2012
DOI: 10.1597/11-007
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Changes after Presurgical Nasoalveolar Molding (PNAM) in the Unilateral Cleft Lip Nose

Abstract: A favorable reshaping of the nose after PNAM was achieved, resulting in an improvement in form before lip surgery. These changes lead to improved nasal symmetry before primary lip and nasal reconstruction in UCLP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 42 publications
4
39
3
2
Order By: Relevance
“…A growing number of cleft centers now offer NAM [5] and research has reported on the benefits of NAM or a similar variation of presurgical orthopedics [6, 7]. For example, patients with unilateral cleft lip who undergo NAM reportedly demonstrate greater nasal symmetry through 9 years of age than patients with unilateral cleft lip who do not have NAM [8].…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of cleft centers now offer NAM [5] and research has reported on the benefits of NAM or a similar variation of presurgical orthopedics [6, 7]. For example, patients with unilateral cleft lip who undergo NAM reportedly demonstrate greater nasal symmetry through 9 years of age than patients with unilateral cleft lip who do not have NAM [8].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] In this study, both techniques effectively reduced alveolar gap and effectively improved nasal symmetry. This improvement was mainly vertical (percentage change in nostril height ratio: 38.4 and 37.9 for the Grayson and Figueroa techniques, respectively; p ϭ 0.916) (Figs.…”
Section: Discussionmentioning
confidence: 91%
“…Among the group of studies that assesses only the nasal molding, 2 studies were included. These reported an improvement of nasal symmetry and alar cartilage depression with NAM before primary surgeries [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%